2019
DOI: 10.1101/750133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eosinophil deficiency promotes aberrant repair and adverse remodelling following acute myocardial infarction

Abstract: Background: Eosinophil count predicts outcome following myocardial infarction (MI) and eosinophils regulate tissue repair and regeneration in extra-cardiac settings.Objectives: To investigate the role of eosinophils in regulating inflammation, repair and remodelling following MI.Methods: Blood eosinophil count was assessed in 732 patients undergoing primary percutaneous coronary intervention for ST-segment elevation MI (STEMI). Experimental MI was induced in wild-type (WT) and eosinophil-depleted mice (ΔdblGAT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The prevailing view of the eosinophil as a purely proinflammatory cell type has been challenged in recent years with a growing number of laboratory mouse studies describing non‐redundant roles in tissue development, homeostasis and repair. This includes a variety of tissues and cell types, for example maintenance of mucosal homeostasis [ 4 ], contractility of blood vessels [ 5 ], control of glucose metabolism in adipose tissue [ 6 ], liver regeneration [ 7 ], and wound healing of injured muscle tissue [ 8 ] including following myocardial infarction [ 9 ]. However, whilst advances have been made in understanding eosinophil contribution to health in laboratory animals, eosinophil functions in humans are largely undefined [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevailing view of the eosinophil as a purely proinflammatory cell type has been challenged in recent years with a growing number of laboratory mouse studies describing non‐redundant roles in tissue development, homeostasis and repair. This includes a variety of tissues and cell types, for example maintenance of mucosal homeostasis [ 4 ], contractility of blood vessels [ 5 ], control of glucose metabolism in adipose tissue [ 6 ], liver regeneration [ 7 ], and wound healing of injured muscle tissue [ 8 ] including following myocardial infarction [ 9 ]. However, whilst advances have been made in understanding eosinophil contribution to health in laboratory animals, eosinophil functions in humans are largely undefined [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils have been reported in pruritic papulovesicular eruptions in a case of generalized vaccinia after smallpox vaccination [ 227 ] and are well described as drivers of allergic diseases such as eosinophilic asthma [ 228 , 229 ]. However, recently a role for eosinophils in tissue repair and wound healing has emerged [ 189 , 190 ], particularly for muscle tissues [ 191 193 ]. That the eosinophils in these resolving post-vaccination lesions are distinct from inflammatory eosinophils is supported by the absence of IL-5 mRNA expression ( S2G Table ), with anti-IL-5 therapy used for eosinophilic asthma [ 230 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, Toor et al. ( 4 ) provided an informative and interesting study that established a protective role for eosinophils in LV remodeling following MI. The investigators defined a potential mechanism of benefit and suggested that modulation of eosinophil cytokine expression favoring IL-4 might be a target for therapeutic intervention.…”
mentioning
confidence: 89%
“…In this issue of JACC: Basic to Translational Science , Toor et al. ( 4 ) examined the role of eosinophils following acute MI. Previous observational studies reported conflicting associations between eosinophil abundance and clinical outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation